Towards a collaborative higher music education curriculum: a singer-composer duoethnography - Lisa Fornhammar; Miika Hyytiäinen (Nordic Research in Music Education)
This duoethnographic study explores the process of developing a collaborative curriculum in higher music education for singers and composers. Drawing from our experiences as a singer and a composer, we investigate the potential of third spaces in fostering interdisciplinary collaboration and breaking institutional silos. We propose a curriculum that integrates co-creation, improvisation, and cross-disciplinary dialogue, emphasizing the beginner’s mindset as a tool for innovation. Our findings contribute to the discourse on collaborative professionalism and expanding professionalism in music education, aiming to support more integrated and dynamic learning environments for future musicians.